Gravity versus magnetic fields in forming molecular clouds - Ibáñez Mejía, Juan Camilo; Mac Low, Mordecai-Mark; Klessen, Ralf S. (The astrophysical journal, 2022)
Magnetic fields are dynamically important in the diffuse interstellar medium. Understanding how gravitationally bound, star-forming clouds form requires modeling of the fields in a self-consistent, supernova-driven, turbulent, magnetized, stratified disk. We employ the FLASH magnetohydrodynamics code to follow the formation and early evolution of clouds with final masses of 3-8 × 103 M ⊙ within such a simulation. We use the code’s adaptive mesh refinement capabilities to concentrate numerical resolution in zoom-in regions covering single clouds, allowing us to investigate the detailed dynamics and field structure of individual self-gravitating clouds in a consistent background medium. Our goal is to test the hypothesis that dense clouds are dynamically evolving objects far from magnetohydrostatic equilibrium. We find that the cloud envelopes are magnetically supported with field lines parallel to density gradients and flow velocity, as indicated by the histogram of relative orientations and other statistical measures. In contrast, the dense cores of the clouds are gravitationally dominated, with gravitational energy exceeding internal, kinetic, or magnetic energy and accelerations due to gravity exceeding those due to magnetic or thermal pressure gradients. In these regions, field directions vary strongly, with a slight preference toward being perpendicular to density gradients, as shown by three-dimensional histograms of relative orientation.
Gesehen am 03.03.2022